Membership in political parties and restrictions related to civil service in the Republic of Belarus - Mikhailovsky, Vadim S. (Journal of the Belarusian State University. Law, 2026)
The article examines legal restrictions on the implementation of state civil (apparatus) service in the Republic of Belarus stipulated by membership in political parties. The article reveals the expediency of membership in political parties of state civil (apparatus) employees in connection with ensuring the high-quality work of civil servants and preventing corruption offenses in the civil service. The relationship between party membership and the political and ideological level of the civil service is analysed. Discretion in state service activities is studied in the context of party membership. A conclusion is made about the influence of passive and active party membership on entry, passage and termination of civil service.
Keywords: civil service; political parties; legal restrictions; fight against corruption; discretion; ideology of the Belarusian state